If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4x + -1y)(2x + -1Y) = 0 Reorder the terms: (4x + -1y)(-1Y + 2x) = 0 Multiply (4x + -1y) * (-1Y + 2x) (4x * (-1Y + 2x) + -1y * (-1Y + 2x)) = 0 ((-1Y * 4x + 2x * 4x) + -1y * (-1Y + 2x)) = 0 ((-4xY + 8x2) + -1y * (-1Y + 2x)) = 0 (-4xY + 8x2 + (-1Y * -1y + 2x * -1y)) = 0 Reorder the terms: (-4xY + 8x2 + (-2xy + 1yY)) = 0 (-4xY + 8x2 + (-2xy + 1yY)) = 0 Reorder the terms: (-4xY + -2xy + 8x2 + 1yY) = 0 (-4xY + -2xy + 8x2 + 1yY) = 0 Solving -4xY + -2xy + 8x2 + 1yY = 0 Solving for variable 'x'. The solution to this equation could not be determined.
| 5x+31=-53-9x | | x*6-4=-40 | | (4x+3Y)(2x+y)= | | 4(x-1)+2(x-7)=127 | | 91-I=72 | | Q(x)=3x-x+3 | | (4x+3y)(4x+y)= | | AB-3=BC-2 | | x-7.4=-5.1 | | 1.6+.6Y+2=.4Y | | (4x-y)(2x+3y)= | | (4x+y)(2x-3y)= | | 1.6+.6Y+2=9 | | 7h-45=46 | | 9-5n+1=21 | | r+31=16 | | 7m-24=25 | | Ab-3=bf-2d | | 8x^3-8x^2+32x-32=0 | | r+3=16 | | 36-4p= | | 9=m+16 | | 8.7=3.6+.6Y | | 3x+4y-2z=20 | | 6.8=3.6+.6Y | | 6.8=3.6+.67 | | 7p+5=9+6p | | 2(1+3m)-3=-(5-2m) | | -3z^4+7z^4=0 | | x+(x-14)=350 | | 3F+-6F-7F+10F^2-8= | | -(2n+1)-2(1+5n)=21 |